TREATMENT OF TYPE 1 DIABETES IN CHILDREN AND ADOLESCENTS: SPECIAL FEATURES AND CHALLENGES (CIPEEX, 2025)
Type 1 diabetes is an autoimmune disease in which the immune system destroys the cells in the pancreas responsible for producing insulin, resulting in a total deficiency of this hormone. Genetic and environmental factors can influence its development, and symptoms include excessive thirst, frequent urination, fatigue, and weight loss. The diagnosis is made through tests such as fasting blood glucose and glycosylated hemoglobin. Treatment involves the use of insulin, a healthy diet, physical exercise, and glucose monitoring. If not properly controlled, the disease can lead to acute and chronic complications. Although prevention is still limited, early diagnosis and proper treatment can improve quality of life, albeit at a high cost. This study aims to analyze the main challenges faced in the treatment of type 1 diabetes, with a special focus on treatment adherence, the emotional impact on patients, especially children and adolescents, and the barriers imposed by the high costs of technologies used in glycemic control, such as insulin pumps and continuous glucose monitors. A narrative literature review was conducted based on 29 publications extracted from the SciELO, PubMed, and Google Scholar databases, considering materials from the last 5 years in Portuguese and English. Of the articles analyzed, two highlighted challenges in the treatment of type 1 diabetes in children and adolescents, such as treatment adherence and emotional management. Technology, such as insulin pumps and continuous glucose monitors, facilitates glycemic control, but costs remain a barrier. Health education, essential for proper management, is not always accessible. Effective treatment depends on overcoming these obstacles, with an emphasis on psychological support and education to improve patients' quality of life. It is concluded that type 1 diabetes is a complex chronic disease, whose effective treatment depends on a multidisciplinary approach that includes the use of insulin, constant glucose monitoring, healthy eating, and psychological support.